2022
DOI: 10.1186/s12877-022-03575-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of a telemedicine programme for preventing unplanned hospitalisations of older adults living in nursing homes: the GERONTACCESS cluster randomized clinical trial

Abstract: Objective The GERONTACCESS trial evaluated the utility and cost-effectiveness of a gerontological telemedicine (TLM) programme for preventing unplanned hospitalisation of residents living in nursing homes (NHs) in regions lacking medical facilities and/or qualified medical providers (“medical deserts”). Design GERONTACCESS was a 12-month, multicentre, prospective cluster-randomised trial conducted in NHs. The intervention group underwent TLM assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Results on LOS showed no signi cant reduction, except in the study by Mudiyanselage et al, [42], when hospitalizations related to acute submission particularly. Despite the potential observed improvement in health service usage, the studies reporting survival and death numbers did not indicate any signi cant improvement [29,34,35,37,43] (see supplementary material 2). Insert Table 7 Quality of Life Signi cant improvements in quality of life of RMS groups were noted in six out of 11 studies, on different quality-of-life scales [32,33,35,39,42,43].…”
Section: Insert Tablementioning
confidence: 99%
See 3 more Smart Citations
“…Results on LOS showed no signi cant reduction, except in the study by Mudiyanselage et al, [42], when hospitalizations related to acute submission particularly. Despite the potential observed improvement in health service usage, the studies reporting survival and death numbers did not indicate any signi cant improvement [29,34,35,37,43] (see supplementary material 2). Insert Table 7 Quality of Life Signi cant improvements in quality of life of RMS groups were noted in six out of 11 studies, on different quality-of-life scales [32,33,35,39,42,43].…”
Section: Insert Tablementioning
confidence: 99%
“…These were included as we are concerned with the existing interventions of the telemonitoring system that involve elderly patients at risk. All but one study, the GERONTACCESS study [37], which focused on nursing home settings, involved home-based remote monitoring. This was included as we are interested in understanding the French approach to remote monitoring for elderly individuals at high risk.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Telemedicine is a safe modality of care and is noninferior in geriatric patients presenting acute medical conditions in cases where they are accompanied on-site by a nursing caregiver [9]. Several studies evaluating geriatric telemedicine have shown a reduced number of emergency department visits and HAs from NHs [10][11][12][13][14][15][16][17][18][19][20][21][22]. Despite these positive effects on the overall level of care and the widespread accessibility of telemedical tools, deployment in primary care and NHs is only progressing slowly.…”
Section: Introductionmentioning
confidence: 99%